Current Practices of Quality Assurance in the College of Business Administration at King Saud University: Faculty Members' Perspectives - Suliman Zakaria Suliman Abdalla; Nasr Ali Mohammed Hatram (University of Science and Technology, Yemen, 2017)
This paper aimed to identify some perspectives of the faculty members and assistants on the practices of quality assurance in the College of Business Administration, King Saud University in order to enhance the college plans toward involving everyone to practice quality as a culture with an ultimate goal to achieve excellence in quality assurance practices at the college. The study was conducted during the second semester of the academic year 1432-1433H and the first semester of the year 1433-1434H. To achieve this purpose, a questionnaire was developed to collect the data from (379) faculty members. Based on using some descriptive and inferential statistics, the results of the paper showed that there was a positive general attitude toward the vision and mission of the college, quality of study programs, college management and quality assurance activities applied by the Vice-Deanship of Development and Quality. It was recommended that the suggestions forwarded by the faculty members should be taken into consideration in order to further improve quality at the college. Keywords: Quality assurance, Academic accreditation, Academic programs, College of Business Administration, King Saud University.